2019
DOI: 10.1002/dev.21893
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood crime risk and resting respiratory sinus arrhythmia in middle childhood: Evidence of gender differences

Abstract: Although there is a robust link between resting respiratory sinus arrhythmia (RSA), a biological marker of emotion regulation, and risk for psychopathology, the factors that may be associated with aberrant RSA development remain unclear. The goal of the current study was to examine the relation between children's resting levels of RSA and neighborhood crime, a macro‐level environmental stressor associated with increased risk for multiple forms of psychopathology in youth. The levels of neighborhood crime were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The results indicated that girls living in neighborhood which had high risk of violent crimes (emotional stimulus) showed decreased RSA compared to boys living in the same neighborhood. The authors attributed this difference to the stronger activation of cortical and limbic structures in females for angry and fearful stimuli in comparison to males (38). Another reason for this difference could be the age of the children.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that girls living in neighborhood which had high risk of violent crimes (emotional stimulus) showed decreased RSA compared to boys living in the same neighborhood. The authors attributed this difference to the stronger activation of cortical and limbic structures in females for angry and fearful stimuli in comparison to males (38). Another reason for this difference could be the age of the children.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is important to account for intervention‐related changes in respiration rates when calculating RSA. However, there is considerable variability in the frequency bands used to calculate RSA in school‐aged children (Dollar et al., 2020; Feurer et al., 2020; Quiñones‐Camacho & Davis, 2018; Ward et al., 2015). Setting an accurate lower bound of the high frequency band is critical to capturing RSA change in response to slow‐paced breathing, which reduces the respiration rate.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we addressed measurement questions that can advance the field of research on children's physiology in the context of deep breathing. First, given the considerable variability in frequency bands used to calculate RSA in elementary school‐aged children (e.g., Dollar et al., 2020; Feurer et al., 2020; Quiñones‐Camacho & Davis, 2018; Ward et al., 2015) and the need to account for lower respiration rate induced by slow‐paced breathing (Shader et al., 2018), we tested whether our results were robust across three different lower frequency bounds used to calculate RSA (i.e., 0.12, 0.15 and 0.20 Hz). In the study preregistration, we observed that the deep breathing intervention could reduce respiration rates to approximately 0.12 Hz.…”
Section: Present Investigationmentioning
confidence: 99%